Exploring the feasibility of collecting music and wellbeing data to examine intentional listening using a mobile-ESM application - McFerran, Katrina Skewes; Krause, Amanda E.; Osborne, Margaret S. (Frontiers in Psychology, 2025)
This brief report describes a small-scale feasibility study investigating the use of mobile Experience Sampling Methodology (ESM) for collecting data on intentionality in music listening for well-being. Sixteen university students used the MuPsych app (Randall and Rickard, 2012) for a 2-week pilot study (resulting in 263 music listening episode responses), with seven participating in semi-structured follow-up interviews. Data was collected at baseline and then triggered by mobile music listening episodes at 0, 5 and 20 min. Baseline measures were of wellbeing; and listening episode data included music choice, purpose, context, and mood. After assigning listeners to languishing, moderate, or flourishing wellbeing categories, differences became apparent in participants’ experiences of listening to music. Several challenges to feasibility were experienced in self-selection and biased reporting by participants as well as technological limitations of data collection techniques. Recommendations for future ESM studies of everyday music listening are offered.